Obligations & contracts : laws, principles and jurisprudence - Domingo, Andrix D. (Coaching for Results Publishing, 2018)
This book is intended for primarily for accountancy students, business students and Certified Public Accountant (CPA) board examination candidates and law students. This work, provide a simplified examples that were incorporated and decisions of Supreme Court and were digested in a simple manner which serve as a tool for easier comprehension of the pertinent articles. Definition of terms used in different articles was integrated to enable the readers to appreciate and comprehend well the meaning of the law.
Keywords: Contracts; Obligations (law)- philippines